2019
DOI: 10.1016/j.sleep.2018.09.011
|View full text |Cite
|
Sign up to set email alerts
|

White matter structural differences in OSA patients experiencing residual daytime sleepiness with high CPAP use: a non-Gaussian diffusion MRI study

Abstract: Objectives: To investigate factors associated with residual sleepiness in patients who were highly adherent to continuous positive airway pressure (CPAP). Nocturnal inactivity, comorbidities, concomitant medications, and, in particular, white matter (WM) differences using diffusion magnetic resonance imaging (MRI) were explored using a continuous-time random-walk (CTRW) model. Methods: Twenty-seven male patients (30–55 years of age) with obstructive sleep apnea (OSA) received CPAP as the only treatment (CPAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 55 publications
2
28
0
2
Order By: Relevance
“…As a final note, providers should be aware that about 20% of patients who are highly adherent to treatment remain sleepy. Mechanisms for this have been proposed, and there is evidence of white matter compromise, with myelin diffusivity affected along with axonal shrinkage, in those who are sleepy compared with adherent patients who are not [33]. Fortunately, in these cases, there are medications that increase alertness with better sustained attention and quality of life [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…As a final note, providers should be aware that about 20% of patients who are highly adherent to treatment remain sleepy. Mechanisms for this have been proposed, and there is evidence of white matter compromise, with myelin diffusivity affected along with axonal shrinkage, in those who are sleepy compared with adherent patients who are not [33]. Fortunately, in these cases, there are medications that increase alertness with better sustained attention and quality of life [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…These changes suggest possible myelin and/or axonal damage. In contrast, whole-brain fractional anisotropy (FA) and axial diffusivity in patients with OSA did not differ between patients with and without EDS ( 32 , 33 ). In the same studies, differences in regional DTI parameters were reported, with higher regional MD (primarily related to increased radial diffusivity) and lower regional FA in patients with EDS compared with those without EDS.…”
Section: Human Imaging Studiesmentioning
confidence: 85%
“…In the same studies, differences in regional DTI parameters were reported, with higher regional MD (primarily related to increased radial diffusivity) and lower regional FA in patients with EDS compared with those without EDS. These differences are suggestive of decreased axonal and myelin integrity ( 32 , 33 ). Specifically, these regional differences were observed in fibers of the corpus callosum, internal and external capsule, corona radiata, and sagittal stratum, with most changes seen in the left hemisphere ( 32 ).…”
Section: Human Imaging Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuous positive airway pressure (CPAP) therapy has been shown to alter DTI metrics on treatment‐naïve subjects when acquired before and after treatment, as well as on measures of cortical blood flow and blood volume . DTI studies have also now been employed to understand why some treatment‐compliant patients remain symptomatic with daytime sleepiness, with such studies revealing persistent white matter changes on DTI which may explain ongoing symptoms, as well as potentially highlight a subgroup at higher risk of future cognitive decline . A longer term study that evaluated brain morphology after 18 months of CPAP therapy in OSA patients found longer treatment correlated with volume increases in the hippocampal dentate gyrus and cerebellar dentate nucleus, and in those with severe OSA, with volume increases in the pre‐frontal cortex .…”
Section: Sleep and Dementiamentioning
confidence: 99%